Chemogenomics and chemical genetics a user's introduction for biologists, chemists and informaticians - Maréchal, Eric; Roy, Sylvaine; Lafanechère, Laurence (Springer, 2011)
aBiological and chemical sciences have undergone an unprecedented transformation, reflected by the huge use of parallel and automated technologies in key fields such as genome sequencing, DNA chips, nanoscale functional biology or combinatorial chemistry. It is now possible to generate and store from tens of thousands to millions of new small molecules, based on enhanced chemical synthesis strategies. Automated screening of small molecules is one of the technologies that has revolutionized biology, first developed for the pharmaceutical industry and recently introduced in academic laboratories. High-throughput and high-content screening allow the identification of bioactive compounds in collections of molecules (chemical libraries), being effective on biological targets defined at various organisational scales, from proteins to cells to complete organisms. These bioactive molecules can be therapeutic drug candidates, molecules for biotech, diagnostic or agronomic applications, or tools for basic research. Handling a large number of biological (genomic and post-genomic), chemical and experimental information, screening approaches cannot be envisaged without any electronic storage and mathematical treatment of the data. ?Chemogenomics and Chemical Genetics"  is an introductory manual presenting methods and concepts making up the basis for this recent discipline. This book is dedicated to biologists, chemists and computer scientist beginners. It is organized in brief, illustrated chapters with practical examples. Clear definitions of billogical, chemical and IT concepts are given in a glossary section to help readers who are not familiar with one of these disciplines. Chemogenomics and Chemical Genetics should therefore be helpful for students (from Bachelor's degree level), technological platform engineers, and researchers in biology, chemistry, bioinformatics, cheminformatics, both in biotech and academic laboratories.